CRISPR/Cas-Based Gene Editing Strategies for DOCK8 Immunodeficiency Syndrome - Ravendran, Sujan; Hernández, Sabina Sánchez; König, Saskia; Bak, Rasmus O. (Frontiers in Genome Editing, 2022)
Defects in the DOCK8 gene causes combined immunodeficiency termed DOCK8 immunodeficien-cy syndrome (DIDS). DIDS previously belonged to the disease category of autosomal recessive hyper IgE syndrome (AR-HIES) but is now classified as a combined immunodeficiency (CID). This genetic disorder induces early onset of susceptibility to severe recurrent viral and bacterial infec-tions, atopic diseases and malignancy resulting in high morbidity and mortality. This pathological state arises from impairment of actin polymerization and cytoskeletal rearrangement, which induces improper immune cell migration-, survival-, and effector functions. Owing to the severity of the dis-ease, early allogenic hematopoietic stem cell transplantation is recommended even though it is asso-ciated with risk of unintended adverse effects, the need for compatible donors, and high expenses. So far, no alternative therapies have been developed, but the monogenic recessive nature of the dis-ease suggests that gene therapy may be applied. The advent of the CRISPR/Cas gene editing system heralds a new era of possibilities in precision gene therapy, and positive results from clinical trials have already suggested that the tool may provide definitive cures for several genetic disorders. Here, we discuss the potential application of different CRISPR/Cas-mediated genetic therapies to correct the DOCK8 gene. Our findings encourage the pursuit of CRISPR/Cas-based gene editing approaches, which may constitute more precise, affordable, and low-risk definitive treatment op-tions for DOCK8 deficiency.